Terrorism and Human Trafficking: A Dark Alliance of Organized Crime - Soltan, Vadim (Acta Universitatis Danubius. Juridica, 2024)
This link between human trafficking and terrorist financing is part of a wider criminal ecosystem where terrorist organizations and trafficking networks collaborate to maximize their profits. Modern terrorist organizations such as ISIS, Boko Haram and Al-Shabaab have been able to exploit power vacuums, local conflicts and social discontent to expand their influence. They use brutal and effective tactics to spread terror and achieve their ideological and political goals. Analyzing them is essential for understanding the dynamics of contemporary terrorism and for formulating effective strategies to combat it.